Oxidative stress‐induced phosphorylation of JIP4 regulates lysosomal positioning in coordination with TRPML1 and ALG2. (11th October 2022) - Sasazawa, Yukiko; Souma, Sanae; Furuya, Norihiko; Miura, Yoshiki; Kazuno, Saiko; Kakuta, Soichiro; Suzuki, Ayami; Hashimoto, Ryota; Hirawake‐Mogi, Hiroko; Date, Yuki; Imoto, Masaya; Ueno, Takashi; et al.
Abstract: Retrograde transport of lysosomes is recognised as a critical autophagy regulator. Here, we found that acrolein, an aldehyde that is significantly elevated in Parkinson's disease patient serum,  enhances autophagy by promoting lysosomal clustering around the microtubule organising centre via a newly identified JIP4‐TRPML1‐ALG2 pathway. Phosphorylation of JIP4 at T217 by CaMK2G in response to Ca 2+ fluxes tightly regulated this system. Increased vulnerability of JIP4 KO cells to acrolein indicated that lysosomal clustering and subsequent autophagy activation served as defence mechanisms against cytotoxicity of acrolein itself. Furthermore, the JIP4‐TRPML1‐ALG2 pathway was also activated by H2 O2, indicating that this system acts as a broad mechanism of the oxidative stress response. Conversely, starvation‐induced lysosomal retrograde transport involved both the TMEM55B‐JIP4 and TRPML1‐ALG2 pathways in the absence of the JIP4 phosphorylation. Therefore, the phosphorylation status of JIP4 acts as a switch that controls the signalling pathways of lysosoma l distribution depending on the type of autophagy‐inducing signal. Synopsis: Lysosome repositioning towards the microtubule organizing centre (MTOC) contributes to autophagy activation. This study shows that acrolein, an aldehyde elevated in Parkinson's disease patients' serum, promotes lysosomal retrograde transport via lysosomal recruitment of the dynein adaptor JIP4. Acrolein levels are elevated in Parkinson's disease patients' serum. Acrolein enhances autophagy by promoting lysosomal clustering around MTOC. Acrolein induces JIP4 phosphorylation by CaMK2G and JIP4 recruitment to the lysosomes in a TRPML1/ALG2‐dependent manner. Acrolein induced‐lysosomal clustering and subsequent autophagy act as a defence response against oxidative stress. Abstract : Acrolein, an aldehyde elevated in the serum of Parkinson's disease patients, promotes autophagy via lysosomal recruitment of the dynein adaptor JIP4.